Plant-aided Desalination System: A Preliminary Study - Katsumi Ohyama; Kaori Niki; Erdoo P. Awai (HortTechnology)
Although 70% of the Earth’s surface area is covered with water, 97% of this water is unusable because of salinity. Challenges with existing freshwater scarcity can be mitigated by investigating methods to convert saltwater into freshwater. We developed a lettuce plant-aided solar desalination system based on the basin method to harvest fresh water. The system comprises a lettuce (Lactuca sativa L.) plant community, white light-emitting diodes for simulating sunlight, a thermally insulated box equipped with a cooling system, and a CO2 gas cylinder. This system can harvest freshwater with low electric conductivity using artificial seawater with less than 20% of the specified concentration. Compared with conventional solar desalination systems based on the basin method, the proposed desalination system can harvest greater amounts of freshwater. The amount of harvested freshwater increases by decreasing the CO2 concentration because of photosynthesis in the lettuce plant community. The results suggest that lowering the CO2 concentration can increase the amount of harvested freshwater, which is the main objective of the desalination system. Further, the results suggest that the CO2 concentration should be maintained at around atmospheric standard levels (approximately 500 µmol·mol−1) if both the freshwater and plants are to be harvested.